First principles investigations of electronic structures and hyperfine interactions of Muonium in tetraphenylsilane / Pek-Lan Toh ... [et al.] - Toh, Pek-Lan; Sulaiman, Shukri; Mohamed-Ibrahim, Mohamed Ismail; Jayasooriya, Upali A. (2012)
In this study, the equilibrium structures of muoniated-tetraphenylsilane (SiPh4-Mu) were stabilized using the first principle investigations employing the Density Functional Theory (DFT) technique. Three Muonium (Mu) trapping sites were considered in the investigations, namely ortho, meta, and para positions on one of phenyl rings. The geometry optimizations for all the systems leading to local energy minima were investigated. The calculated total energy of all the systems were very similar, with the differences of energy being only 0.04 eV lower between the para case and the other two cases. With the DFT procedure, the Mu hyperfine interactions were examined. The major contribution to the Mu hyperfine interactions was from isotropic component with the corresponding values of 441.28 MHz, 452.21 MHz, and 453.78 MHz for the ortho, meta, and para cases, respectively. The anisotropic component was also predicted and it was more and less 6 MHz for all three sites.